Analysis of The Influence of Car, NPL, NIM, BOPO, and IDR on ROA at PT. Yogyakarta Special Regional Development Bank (BPD DIY) Period 2015-2022 - Yhusofi Whidastira; Syamsul Bakri; Khanifa, Fadhla (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
The availability of banks is increasingly diverse and increasing in number, people can choose from the many banks in Indonesia. The large number of banks means that people have to be more careful in choosing the right bank. It is important to be able to assess bank performance, especially for potential investors. This research aims to determine the effect of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Net Interest Margin (NIM), Operating Expenses on Operating Income (BOPO), and Loan to Debt Ratio (LDR) on profitability, namely Return On Assets (ROA) at Bank BPD DIY 2015-2022. The data used are ratios from the Quarterly Financial Reports of Bank BPD DIY from 2015-2022, totaling 32 data samples for each variable. The research method used is descriptive analysis and linear regression analysis. The research results show that CAR, NPL, NIM, BOPO, and LDR simultaneously have an influence on ROA. Partially, NIM has a positive effect on ROA and BOPO has a negative effect on ROA. Meanwhile, CAR, NPL and LDR have no effect on ROA.